Toxic and deterrent effects of natural products against Cnaphalocrocis medinalis (Guenee) (Lepidoptera: Crambidae) (Indian Journal of Traditional Knowledge (IJTK), 2025)
The inhibitory and lethal effects of natural pest management products were observed against rice leaf folder, C. medinalis, during 2022 and 2023, under both laboratory and field conditions at the Department of Organic Agriculture and Natural Farming, CSK Himachal Pradesh Krishi Vishvavidyalaya, Palampur. Agniastra, Brahmastra, Darekastra, Dashparni ark, and Neemastra were the products which were made and used for pest management studies. The LC50 values ranged from 26.56 (Dashparni ark) to 62.13% (Brahmastra). Dashparni ark showed the highest repellent activity with a repellence index (RI) of 0.48 and the highest feeding deterrence with a feeding deterrence index (FDI) of -70.01 at 40% concentration. When given a choice, Neemastra was least preferred by C. medinalis for oviposition, in the choice test at all concentrations compared to when no choice was given. Field evaluations data of two years, further confirmed the efficacy of Dashparni ark by reducing C. medinalis infestations by 62.82 and 66.49% over untreated controls in both years, respectively. These findings suggest that natural products, especially Dashparni ark and Neemastra, could be effective and eco-friendly alternatives to chemical pesticides for managing C. medinalis in rice cultivation.